Reliability of System Identification Technique in Super High-Rise Building - Ikeda, Ayumi; Fujita, Kohei; Takewaki, Izuru (Frontiers in Built Environment, 2015)
A smart physical-parameter based system identification method has been proposed in the previous paper. This method deals with time-variant nonparametric identification of natural frequencies and modal damping ratios using ARX (Auto-Regressive eXogenous) models and has been applied to high-rise buildings during the 2011 off the Pacific coast of Tohoku earthquake. In this perspective article, the current state of knowledge in this class of system identification methods is explained briefly and the reliability of this smart method is discussed through the comparison with the result by a more confident technique.